Heroes of the dawn Celtic myth - Duncan Baird Publishers (Amsterdam Time-Life Books, 1996)
Enter the Celtic world of gods, goddesses, & the cosmos, where King Arthur pulled a sword from a stone. Here, with maps & historical overviews, are some of the most powerful & unforgettable Celtic stories ever told. A dramatic series that captures, culture by culture, the information that never makes it into the history books: strange stories, mystic rites, angry gods, vision quests.
The Celtic world -- Gods, goddesses and the cosmos -- Battles of the heroes -- Tales of magic and transformation -- Legends of Arthur -- The legacy of the Celts.
Includes bibliographical references (page 144) and index.
FA-2881g donated by Reynaldo G. Alejandro.
Keywords: Mythology, Celtic; Celts -- History